2007
DOI: 10.1111/j.1745-7262.2007.00085.x
|View full text |Cite
|
Sign up to set email alerts
|

Sildenafil versus continuous positive airway pressure for erectile dysfunction in men with obstructive sleep apnea: a comparative study of their efficacy and safety and the patient's satisfaction with treatment

Abstract: Both sildenafil 100 mg and CPAP, used separately, had positive therapeutic impact but sildenafil was superior. Patients and their partners were more satisfied with sildenafil for the treatment of ED. However, because of the high proportion of dissatisfied men and partners, new therapeutic agents or a combination of the two methods must be studied further.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
41
0
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(44 citation statements)
references
References 19 publications
0
41
0
2
Order By: Relevance
“…In another study, sildenafil increased CPAP effectiveness in patients with mild OSAS when compared with CPAP alone. 6 In contrast, in study by Margel et al, 28 CPAP treatment deteriorated erectile function. This may be due to the improper use of CPAP.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…In another study, sildenafil increased CPAP effectiveness in patients with mild OSAS when compared with CPAP alone. 6 In contrast, in study by Margel et al, 28 CPAP treatment deteriorated erectile function. This may be due to the improper use of CPAP.…”
Section: Discussionmentioning
confidence: 91%
“…Consequently, without defining the cause of ED, many drugs such as sildenafil are used for treatment. 13 The use of sildenafil with CPAP was reported by Perimenis et al, 6 whereas Margel et al 28 reported the long-term effects of CPAP treatment on ED in patients with OSAS. The latter study showed that only 20% of patients with OSAS might show improved erectile function solely with CPAP treatment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, RCTs comparing the effect of CPAP to sildenafil showed that both improved erectile function but sildenafil was superior. 147,[149][150][151] There are no RCTs that assessed the impact of CPAP on erectile dysfunction in patients with T2D but one uncontrolled study showed that CPAP for 3 months had no effect on sexual function in 35 men with T2D.…”
Section: Impact Of Continuous Positive Airway Pressurementioning
confidence: 99%